2021
DOI: 10.1039/d1ra03037j
|View full text |Cite
|
Sign up to set email alerts
|

Prospective application of diethylaminoethyl cellulose (DEAE-cellulose) with a high adsorption capacity toward the detoxification of 2,4-dichlorophenoxyacetic acid (2,4-D) from water

Abstract: Dextoxification of 2,4-D was achieved using DEAE-cellulose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The farm water characteristics and the location coordinates have been reported previously by our group in an earlier study. 53 Approximately, a 25 L volume of water was sampled from an agricultural field having a total hardness of over 1000 ppm and a near neutral pH. The pesticide 4,4′-DDT was not present as such in the sample and hence the adsorption experiments was done by spiking 4,4′-DDT at different concentrations and was found that 90% (Table S3 † ) of 4,4′-DDT was adsorbed onto this hybrid adsorbent surface.…”
Section: Resultsmentioning
confidence: 99%
“…The farm water characteristics and the location coordinates have been reported previously by our group in an earlier study. 53 Approximately, a 25 L volume of water was sampled from an agricultural field having a total hardness of over 1000 ppm and a near neutral pH. The pesticide 4,4′-DDT was not present as such in the sample and hence the adsorption experiments was done by spiking 4,4′-DDT at different concentrations and was found that 90% (Table S3 † ) of 4,4′-DDT was adsorbed onto this hybrid adsorbent surface.…”
Section: Resultsmentioning
confidence: 99%
“…In DEAE cellulose, diethylaminoethyl groups replace some of the hydrogen atoms in hydroxyl groups. Ion exchange chromatography separates mixture components via the reversible interaction of ionizing agents with the sorbent's ionic groups [37]. Polysaccharides are eluted from the column using salt solutions of varying concentrations.…”
Section: Separation and Purification Of Polysaccharidesmentioning
confidence: 99%
“…There are several types of adsorbents developed towards the removal of 2,4-D from water with good absorption capacity, e.g., 3dimensional/graphene oxide/Fe 3 O 4 (Hajighasemkhan et al 2022 ), Fe-Zr-based metal–organic frameworks (Liu et al 2022 ), glutaraldehyde-crosslinked chitosan (Li et al 2023 ), bifunctional porous polyethyleneimine-grafted lignin microspheres (Wu et al 2021 ), modified bentonite clay (de Souza and dos Santos 2022 ), diethylaminoethyl cellulose (Kodali et al 2021 ), and UiO-66-NMe 3 + (Wu et al 2020 ). Nevertheless, many of these adsorbent materials show drawbacks like, harsh preparation conditions, high energy consumption, particle agglomeration, and low adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%